(untitled) (Fiep Bulletin - online, 2011)
Volleyball modern features as a sport extremely dynamic. Players are becoming taller, with a greater physical potential and the technical and tactical actions with more complex requirements. Therefore, these facts create the need to increase both the quality and quantity of training, in order to reach a more efficient technical and tactical as well as an increased level of motor skill strength, which is an aspect of physical condition for determining the income shares of the athletes. Besides determining the ability to jump, jump tests provide information about the characteristics of neuromuscular behavior of the lower limbs. The aim of this study is to determine the jump height and contact time through the Drop Jump technique before and after a volleyball match. In the present study, the technique will be used DJ. From this jump can measure the ability to jump from the lower limbs using the Elongation Cycle - Shortening. Since the majority of techniques inherent to volleyball vertical jump involves performing eccentric actions followed by concentric actions, which manifests itself in the CAE. The sample of this research with the participation of nine volleyball players, members of a men’s team were divided into two groups according to income heel DJ. The group with a time of great fall of 50 cm (n = 3) and group 2 with optimum height of 40 cm (n = 6). According to the results of this study it was concluded that there is significant difference between the mean jump height before and after the game for the sample group studied. There was no significant difference in contact time before and after the game in the jumping test DJ.